PERLINDUNGAN HUKUM TERHADAP PEMILIK TANAH DARI PIHAK YANG MENGAMBIL TANAH SECARA ILEGAL DI KABUPATEN TAPANULI TENGAH - Mahmud Effendi, Bonanda Japatani Siregar (YAPEKAM, 2026)
While Indonesian agrarian law guarantees protection of land rights, the reality on the ground shows that land conflicts still frequently occur, both between individuals, individuals and corporations, and between communities and the government. One of the most prominent problems is the rampant illegal land acquisitions, where parties lacking legal grounds take control of others' land through illegitimate means, such as document forgery, intimidation, and even physical violence. Several cases have occurred where outsiders have obtained land title certificates for plots of land long occupied by local residents simply because of connections with National Land Agency (BPN) officials or through non-transparent administrative transactions, practices of manipulating legal and physical data in land registration, resulting in dual ownership status that ultimately triggers legal disputes. The objectives of this study are: a) What is the legal protection for landowners from illegal land acquisitions in Central Tapanuli Regency? b) What is the legal protection for landowners from illegal land acquisitions in Central Tapanuli Regency? What are the factors causing illegal land acquisition in Central Tapanuli Regency and c). How are land disputes resolved between legal owners and those who control them illegally? The research findings are that legal protection for land owners has been regulated in the UUPA and other statutory provisions. However, sociological facts have found various factors that cause legal protection to be ineffective due to legal certainty factors where the owners from generation to generation cannot prove the legitimacy of their land while illegal land owners by exploiting their financial power and corrupt BPN employees collude so that ownership certificates are issued which ultimately lead to disputes. Other factors include the low legal awareness of the community in managing land ownership which affects the data available at the BPN, as well as land administration that is still not organized and weak supervision and no synergy with village or sub-district heads. For legal certainty regarding disputes arising from illegal land ownership, settlement can be carried out through litigation and non-litigation, both of which have advantages and disadvantages. Because Indonesia still recognizes customary law as living law, there must be a division of dispute resolution into customary courts (mediation) and state courts (PN or PTUN). One of the most fundamental preventive measures is strengthening the land registration system. Systematic and comprehensive land registration can provide legal certainty regarding land ownership status, thereby minimizing overlapping rights. Land registration programs such as the Complete Systematic Land Registration (PTSL) implemented by the government are concrete efforts to create an accurate and integrated land database.